Green pawn financing for MSMEs as an ESG-oriented transformation of pawnshop - Muhammad Rifky Apriansyah; Ahadina Hanifati Amimah; Aubry Fairuza Akifa Prabowo (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The transformation of the national financial sector following the implementation of Law No. 4/2023 and its derivative regulations, marks a new phase in strengthening the institutional role of Pegadaian as a key actor in microfinance in Indonesia. In the context of sustainability and ESG (Environmental, Social, and Governance), there is no pawn-based microfinance scheme that proactively targets green MSMEs, even though the potential and demand for green financial products continue to increase. Methods: This article aims to analyze the institutional feasibility and concept of Green Pawn Financing, which is a pawn financing scheme based on ESG principles, while identifying the potential and challenges of its implementation. This study uses a descriptive-analytical approach with a normative institutional review. Institutional innovation theory, sustainable regulatory frameworks, and green financial inclusion literature are used as the basis for analysis. Findings: The results of the study show that Pegadaian already has an adequate initial foundation through gold savings, electric vehicle loans, and a corporate ESG roadmap. However, the integration of ESG into pawn services is not yet systemic and does not explicitly target green MSMEs. This creates a strategic gap that